Study on Antidiabetic Potential of Sessuvium Portulacastrum Aqueous Extract: An In-Silico and In-Vitro Analysis - Mukundh S Tarun; Natarajan Sathan R; Veeraraghavan Vishnu Priya (Wolters Kluwer Medknow Publications, 2024)
Diabetes mellitus is a persistent metabolic condition marked by elevated blood glucose levels due to compromised insulin secretion or functionality. The search for natural antidiabetic agents has gained attention due to their potential effectiveness and safety profiles. Sessuvium portulacastrum, a coastal plant, has been traditionally used for various medicinal purposes. This study investigates the antidiabetic potential of Sessuvium portulacastrum aqueous extract by analyzing its inhibitory effects on key enzymes involved in carbohydrate metabolism and exploring its molecular interactions with critical target proteins. The aqueous extract of Sessuvium portulacastrum was prepared and used for in vitro analysis. The reduced activity of the extract against α-amylase and α-glucosidase enzymes, crucial in glucose absorption and postprandial hyperglycemia, was assessed. Molecular docking techniques were employed to explore the potential interactions between active compounds in the extract and diabetes-related proteins, including BAX, GSK3β, and CADH. The study revealed significant inhibition of both alpha-amylase and alpha-glucosidase enzymes by Sessuvium portulacastrum aqueous extract, indicating its potential to reduce glucose absorption and postprandial hyperglycemia. Moreover, the molecular docking analysis demonstrated strong binding interactions between active compounds in the extract and key proteins involved in diabetes-related pathways, namely apoptotic pathways, glycogen synthesis, and cell adhesion. The findings of this study highlight the promising antidiabetic potential of Sessuvium portulacastrum aqueous extract. Upcoming research should get an attention on isolating and characterizing the active compounds responsible for these effects on antidiabetic therapies from natural sources.